The healthcare experiences of women with cardiac disease in pregnancy and postpartum: A qualitative study - Jane Hutchens; Jane Frawley; Elizabeth A. Sullivan (Wiley, 2022)
Abstract Introduction Cardiac disease affects an estimated 1%-4% of all pregnancies and is a leading cause of maternal morbidity and mortality. There is a lack of data on the healthcare experiences of affected women to inform health service delivery and person‐centred care. This study sought to explore and understand the healthcare experiences of women with cardiac disease in pregnancy and postpartum. Methods This qualitative study used semi‐structured interviews with women who had cardiac disease in pregnancy or the first 12 months postpartum. Data were analysed using thematic analysis. Results Participants were 25 women with pre‐existing or newly diagnosed acquired, genetic and congenital cardiac disease. Analysis of the interviews highlighted the discrepancy between care aspirations and experiences. The participants had a wide range of cardiac diseases and timing of diagnoses, but had similar healthcare experiences of being dismissed, not receiving the information they required, lack of continuity of care and clinical guidelines and of feeling out of place within a healthcare system that did not accommodate their combined needs as a mother and a cardiac patient. Conclusion This study identified a lack of person‐centred care and responsiveness of the healthcare system in providing fit‐for‐purpose healthcare for women with complex disease who are pregnant or new mothers. In particular, cardiac and maternity care providers have an opportunity to listen to women who are the experts on their emergent healthcare needs, contributing to development of the knowledge base on the healthcare experiences of having cardiac disease in pregnancy and postpartum. Patient or Public Contribution Public and patient input into the value and design of the study was gained through NSW Heart Foundation forums, including the Heart Foundation's women's patient group.